Social engagement : a novel - Forrey, Avery Carpenter (Mariner Books, 2023)
Twenty-nine-year-old Callie Holt, with her seven-hour-old marriage already imploded, turns to her phone, sifting through the photographic evidence of the past year to pinpoint where it all went wrong, in this darkly humorous novel exploring millennial wedding culture, class and relationships told through a social media lens.